Monopsony in the Labor Market: New Empirical Results and New Public Policies - Orley Ashenfelter; David Card; Henry S Farber; Michael R. Ransom (Institute of Labor Economics (IZA), 2021)
This paper summarizes the results of nearly a dozen new papers presented at the Sundance Conference on Monopsony in Labor Markets held in October 2018. These papers, to be published as a special issue of the Journal of Human Resources, study various aspects of monopsony and failures of competition in labor markets. It also reports on the new developments in public policies associated with widespread concerns about labor market competition and efforts to ameliorate competitive failures. The conference papers range from studies of the labor supply elasticity individual firms face to studies of local labor market concentration to studies of explicit covenants suppressing labor market competition. New policies range from private and public antitrust litigation to concerns about the effect of mergers and inter-firm agreements on labor market competition. We provide a detailed discussion of the mechanics of the Silicon Valley High Tech Worker conspiracy to suppress competition based on Court documents in the case. Non-compete agreements, which are not enforceable in three states already, have also come under scrutiny.
Keywords: J0; J2; J3; L4; 330; monopsony; labor market power